Post-Surgical Outcomes and Complication Patterns in Lens-Induced Glaucoma: A Prospective Observational Study from South India - Dr Makkena Mani Shankar; Dr Palaboina Rupanjali Yadav; Dr N.Shivani; Dr Mamillapally Harshitha Reddy; Dr Donuru Sanjana Reddy; Dr Donuru Sanjana Reddy; Dr Narayan.M (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Lens-induced glaucoma (LIG) is an important cause of secondary glaucoma in developing countries, usually occurring in association with neglected cataracts and presenting with a sudden rise in intraocular pressure (IOP). Despite advances in cataract surgery, delayed presentation and intervention remain major barriers to achieving good visual prognosis. Aim: This study assesses post-surgical visual outcomes and complication rates in various subtypes of LIG. Objective: To study the different types of LIG, preoperative clinical features, postoperative complications, and visual outcomes following cataract extraction. Methods: A prospective observational study including 80 patients (age >45 years) with clinically confirmed LIG was conducted at PESIMSR, Kuppam, over 18 months. All patients underwent cataract extraction with IOL implantation. Outcomes were evaluated at day 1, week 1, and week 4 post-surgery, focusing on changes in intraocular pressure (IOP), visual acuity, and surgical complications. Results: Phacomorphic glaucoma was the most common subtype (48.75%), followed by phacolytic (30%). The mean pre-op IOP (38.59 ± 8.91 mmHg) significantly reduced to 16.69 ± 3.91 mmHg at 4 weeks (p < 0.05). Visual acuity improved markedly, with 65% achieving 6/6–6/24 vision. Corneal edema (31.25%) was the most frequent complication. A significant association was found between LIG subtype and complication incidence (p = 0.02). Conclusion: Cataract surgery provides favorable visual outcomes in LIG if performed timely. Early diagnosis and aggressive post-op management are key in minimizing complications and preventing irreversible vision loss.